Estudos do texto e do discurso no Brasil - Barros, Diana Luz Pessoa de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The paper draws the distinction between Text and Discourse studies and relates the field to the other area of Linguistic studies developed in Brazil, giving special attention to the aproaches taken.